Influence Firm Size, Leverage, and Fixed Assets Intensity Intax Avoidance - Ni Putu Mayra Pradnya Dewi; Ni Luh Supadmi; Ni Kadek Wahyuni Merta Sari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Tax avoidance is a strategy carried out by business entities to minimize the burden of tax payable by exploiting legal loopholes in the taxation system without explicitly violating applicable provisions. This practice, although legal, poses a serious challenge for the government in optimizing state revenues. This study aims to empirically test the effect of company size (firm size), company funding structure as measured by leverage, and fixed asset intensity on the level of tax avoidance in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. The sample selection was carried out using a purposive sampling technique, resulting in 73 companies as research samples with a total sample size of 292 sample . Data analysis was carried out using the multiple linear regression method with the help of SPSS version 25 software. The results of the study indicate that company size has a positive effect on tax avoidance, while leverage and fixed asset intensity have no effect on tax avoidance.